Introduced leaf beetles of the Maritime Provinces, 7: Cassida rubiginosa Muller and Cassida flaveola Thunberg (Coleoptera: Chrysomelidae) - Majka, Christopher G.; Lesage, Laurent (Zootaxa, 2008)
Cassida rubiginosa Müller is newly recorded in Nova Scotia and on Prince Edward Island. Cassida flaveola Thunberg is newly recorded in Nova Scotia, on Prince Edward Island, and in the Maritime Provinces as a whole. The systematics, identification, introduction history, distribution, zoogeography, biology, parasitism, predation, host plant preferences, and biocontrol potential of both species are surveyed in detail. Early records of C. flaveola are also recounted and questions are posed with respect to its presence and origins in the region and whether it may have been introduced via human agency. Although previously considered an introduced Palearctic species, recent evidence indicates that C. flaveola is, at least in part, a native species with a Holarctic distribution.